The prevalence of thyroid nodules in children with family history for nodular goiter - Hakan Aylanç; Zuhal Aşık (SERNEV, 2017)
Introduction: There is insufficient study on the geneticclustering of nodular goiter. Although twin studies have proved geneticclustering, there is no prospective study on this topic. The aim of this studyis to investigate the existence of familial clustering by evaluating theprevalence of thyroid nodules in the children of families with nodular goiter.Methods: The prevalence of thyroid nodules was calculated byevaluating the thyroid ultrasound results of children from families with andwithout nodular goiter.Results: Nodular goiter was detected in 5 children (3.4%), 2(2.5%) from families with nodular goiter history and 3 (4.7%) from the controlgroup. There was no statistically significant difference between these twogroups.Conclusions: This is the first prospective study to investigatethe familial aspect of nodular goiter disease. In our study, children withnodular goiter were the target group. Following statistical analysis,clustering of nodular goiter was observed in the children of patients withmultinodular goiter.